Temporomandibular joint involvement in juvenile idiopathic arthritis: treatment with an orthodontic appliance - M. Gattinara; V. Gerloni; P. Ghiringhelli; C. Bellintani; G. Farronato; F. Fantini (PAGEPress Publications, 2011)
Introduction and purpose: About 65% of children suffering from juvenile idiopathic arthritis (JIA) shows a more or less marked involvement of temporo-mandibular joint (TMJ) with altered mandibular growth, resorption of the condyles, occlusary instability, reduced chewing ability and facial dysmorphia. The purpose of our study is to prevent and to treat the progressive evolution of JIA on craniofacial growth and morphology with a functional appliance; surgery should be considered only in so far as the adequacy of TMJ movement is concemed. Methods: From 1992 until now 72 children with proved JIA and TMJ involvement have been treated (50 females, 22 males, aged 6 to 16 years old). TMJ involvement was bilateral in 61% and unilateral in 39% of patients. A diagnostic workup was carried out involving tomograms of TMJ and cephalometric radiograph and analysis. The authors used a bimaxillary activator in the attempt to modify the unfavourable growth pattern and provide a gradual ante-rotation of the jaw. Results: Almost all JIA patients showed satisfactory long term results, easing of pain, reduced skeletal discrepancy, increased function and good facial profile. Conclusions: The long term results of this study indicate that orthopaedic therapy might control the vicious circle of the malocclusion in children with JIA, preventing exacerbation of mandibular clockwise rotation. Surgical intervention for the improvement of TMJ function should be considered only if a severe restricted state is imminent.